Development of an antimicrobial wound dressing by co-electrospinning bacteriocins of lactic acid bacteria into polymeric nanofibers - Heunis, Tiaan de Jager (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.